Diet of fish (Characiformes: Characidae) during early developmental stages in the Upper Paraná river basin, Brazil - Claudemir Martins Soares; Carmino Hayashi; Anna Christina Esper Faria-Soares; Eliana Maria Galdioli; Telma Soares (Acta Scientiarum. Biological Sciences, 2017)
This study analyzed the diet during early developmental stages of Astyanax lacustris (AA), Piaractus mesopotamicus (PM), Megaleporinus obtusidens (MO) and Prochilodus lineatus (PL), under experimental conditions. Fish larvae, 350 of each species, were stocked separately in 16 fiber-cement tanks (500 L), from which, three larvae of each species were collected every three days, for 36 days. Tanks were fertilized (1.5 g NPK-7: 14: 8) and had 50% of the surface with macrophytes. Larvae were grouped in age classes = I: 5 to 11, II: 14 to 20, III: 23 to 29 and IV: 32 to 38 days and, dissected for analysis of the digestive tract. Methodologies of dominance, frequency of occurrence and points of food items were used. For AA and PM larvae, measurements were taken for the number and size of organisms to determine the percent participation in biovolume. Changes in diets of larvae in different age classes were found as well as between different species, with the same age. Rotifers were dominant in the content of digestive tracts of all species at Class I, and the larvae diets became more distinct with increasing age, in which AA consumed mainly rotifers, PM, larger organisms (mainly cladocerans), PL, algae (diatoms as the main item) and PP with a more diversified diet (rotifers, ostracodes and algae). In conclusion, early stages of these species presented distinct diets, undergoing remarkable changes in the first 38 days of life.